2019
DOI: 10.1186/s12887-019-1468-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in objectively measured physical activity after a multidisciplinary lifestyle intervention in children with abdominal obesity: a randomized control trial

Abstract: Background Physical activity (PA) is associated with changes in body composition that affect insulin sensitivity and leptin levels. Few studies have assessed the effect of lifestyle interventions on changes in objectively measured PA levels in obese children. To evaluate the effects of a multidisciplinary lifestyle intervention on anthropometric indices, biochemical parameters and accelerometer measured PA in abdominal obese children. Methods A randomized control trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Moderate-to-vigorous physical activity was assessed at baseline using triaxial accelerometry (Actigraph wGT3X-BT, Actigraph LLC, Penascola, FL, USA). Briefly, participants wore the accelerometer around the non-dominant waist for four days, including, at least, two weekend days, as described elsewhere [21]. Accelerometry data were analysed using ActiLife 6.0 software (Actigraph LLC, Penascola, FL, USA) as describe elsewhere [22].…”
Section: Methodsmentioning
confidence: 99%
“…Moderate-to-vigorous physical activity was assessed at baseline using triaxial accelerometry (Actigraph wGT3X-BT, Actigraph LLC, Penascola, FL, USA). Briefly, participants wore the accelerometer around the non-dominant waist for four days, including, at least, two weekend days, as described elsewhere [21]. Accelerometry data were analysed using ActiLife 6.0 software (Actigraph LLC, Penascola, FL, USA) as describe elsewhere [22].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, lifestyle changes (exercise, diet control) can reduce anthropometric indexes in patients with abdominal obesity and these interventions are focused on improving fat consumption and metabolism capacity. [ 38 ] Also, moxibustion and lifestyle changes have many other advantages, including low-cost, stable efficacy, and low risks of complications. Although some studies confirmed such beneficial effects of moxibustion or lifestyle changes in improving abdominal obesity symptoms, the combined effects of moxibustion, and characteristic lifestyle intervention of TCM which includes lifestyle changes on abdominal obesity still remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The IGENOI study (Intervention of Grupo Estudio Navarro de Obesidad Infantil) is a randomized controlled trial (ClinicalTrials.gov, Identifier: NCT03147261) consisting of a 2-year outpatient program based on the Mediterranean diet, physical activity, and nutritional education [19][20][21]. Participants (aged 7 to 16 years) were recruited from the Paediatric Endocrinology Units at both Clínica Universidad de Navarra and Complejo Hospitalario de Navarra, in Pamplona, Navarra, Spain.…”
Section: Methodsmentioning
confidence: 99%